Strategi Eksistensi Umkm Kota Lubuklinggau Pada Masa Pandemi Covid-19 - Rian Oktavianie; Miftahul Jannah; Anggia Syafitri; Indah Puspa Gumilang; Rosalinda Rosalinda (UNIVED Press, 2023)
This study aims to identify and analyze exsistence strategies MSMEs Lubuklinggau City in covid-19 pandemic. The method used in Proporsional Random Sampling. The results of this study are so that MSMEs can survive in the face of the covid-19 pandemic, they can open new product lines and innovate to make new products following developments during the covid-19 pandemic. MSMEs changing the sales model from conventional to online system or e-commerce, in carrying out promotional strategies using digital marketing and building a branding to introduce their products. The application of digital marketing can increase sales. This is so because consumers are wider, closer, can check the quality and reputation of the product, and can make transactions online as they Wish.